Tspan9 Induces EMT and Promotes Osteosarcoma Metastasis via Activating FAK-Ras-ERK1/2 Pathway - Shao, Shijie; Piao, Lianhua; Wang, Jiangsong; Guo, Liwei; Wang, Jiawen; Wang, Luhui; Tong, Lei; Yuan, Xiaofeng; Han, Xu; Fang, Sheng; Zhu, Junke; Wang, Yimin (Frontiers in Oncology, 2022)
Object At present, there are few effective treatment options available to patients suffering from osteosarcoma (OS). Clarifying the signaling pathways that govern OS oncogenesis may highlight novel approaches to treating this deadly form of cancer. Recent experimental evidence suggests that the transmembrane protein tetraspanin-9 (Tspan9) plays a role in tumor development. This study was thus formulated to assess the molecular role of Tspan9 as a regulator of OS cell metastasis. Methods Gene expression in OS cell lines was evaluated via qRT-PCR, while CCK-8, colony formation, Transwell, and wound healing assays were used to explore the in vitro proliferative, invasive, and migratory activities of OS cells. The relationship between Tspan9 and in vivo OS cell metastasis was assessed by injecting these cells into the tail vein of nude mice. Interactions between the Tspan9 and integrin β1 proteins were explored through mass spectrometric and co-immunoprecipitation, and Western blotting to assess the functional mechanisms whereby Tspan9 shapes OS pathogenesis. Results Both primary OS tumors and OS cell lines commonly exhibited Tspan9 upregulation, and the knockdown of this tetraspanin suppressed the migration, invasion, and epithelial-mesenchymal transition (EMT) activity in OS cells, whereas Tspan9 overexpression resulted in opposite phenotypes. Tumor lung metastasis were significantly impaired in mice implanted with HOS cells in which Tspan9 was downregulated as compared to mice implanted with control HOS cells. Tspan9 was also found to interact with β1 integrin and to contribute to OS metastasis via the amplification of integrin-mediated downstream FAK/Ras/ERK1/2 signaling pathway. Conclusion These data suggest that Tspan9 can serve as a promising therapeutic target in OS.